CYTOMEGALOVIRAL ENTERITIS: A RARE CAUSE OF SMALL GUT PERFORATION - Ahmed, Maqbool; Saqib, Sohail; Masud, Mannan; Aurangzeb, Aurangzeb; Pervez, Abeerah; Kamal, Zainab; Khan, Raheel (Journal of Ayub Medical College Abbottabad, 2011)
A 47-year-old man was admitted with four months history of pain upper central abdomen associated with passage of 3-4 loose watery stools per day. Abdominal examination revealed soft abdomen with mild tenderness in the para-umbilical region. There was associated hepatomegaly. His Hb% was low, liver and renal functions were deranged. Upper GI endoscopy revealed antral ulcer, and colonoscopy revealed a caecal ulcer, which were biopsied. Liver biopsy was also done. Histopathology report showed evidence of inflammatory colitis and chronic hepatitis, so a diagnosis of inflammatory bowel disease with autoimmune hepatitis was made. He was negative for HIV and hepatitis serology. He was given long list of medicine including steroids but the symptoms did not improve. Two months after admission he developed severe abdominal pain associated with distension. The X-Ray chest revealed pneumoperitoneum and laparotomy was carried out which revealed a small perforation in terminal ileum associated with multiple circular indurated areas ranging from few mm to 1.5 Cm in size with central thinning spread over distal half of small gut and enlarged mesenteric lymph nodes. The biopsy of perforated area revealed cytomegaloviral enteritis. Postoperatively patient developed ARDS and died on 13th postoperative day. Keywords: Cytomegalovirus, CMV, Perforation, ileal